Bullying e homofobia : um estudo com adolescentes de uma escola pública - Rockenbach, Patrícia Bernardi (2014)
This research aimed to investigate, from the Thought’s Organizers Models Theory, the representations of teenagers, in other words, how they think, feel and act in situations of students homophobic bullying, as well as the moral aspects that are related. Considering theories of morality and studies on bullying and adolescence, questionnaires were administered in a public school in Rondonópolis/MT. Teens (43 adolescents) aged 13 to 17 years old answered a questionnaire about what they admire in people and in themselves, if they already assaulted another person and if have been attacked and four other questions for a story, produced by the researcher, which describes a scene of bullying at school. In all answers moral elements as well as the feelings and thoughts about the bullying phenomenon, particularly with respect to victimization, were analyzed. The results showed that adolescents participants know and indicate moral and ethical values as relevant to life. Regarding own experience in bullying situations, most of them have been or still is a victim of bullying (58,14%) and the minority is or was the author of bullying (18,61%). Thought’s organizers models founded in the answers relating to the fictional story of homophobic bullying demonstrate wide variety of thoughts, feelings, meanings and implications of these adolescents, which characterizes the importance of content in the construction of reasoning, in resolution of conflicts and interpretation of reality. It is possible to tell that there are evidences that the perspective of the victim, at the replies, homophobic bullying should be denied or minimized, under the justification to intensify recurrence. This situation also points that there are few positives answers, to foster critical and guarantee of rights by the own student group. It can be said that the group studied, from these data, the bullying is being naturalized in the school, because the actions against aggression, demonstrated by the participants, are negligible. These responses reinforce the importance of changing the educational paradigm, valuing discussions and critical reflection of the school reality.